Getting Listeners Involved: Rádio ás, a Community Web Project - Jedrzejewski, Stanislaw (2014)
[Excerpt] The idea of community is usually associated with radio today in the context of what Bart Cammaerts (2009,635) classifies as a "third type of broadcast, namely participatory radio, complementary to both commercial and public media". Following Ellie Rennie (2006, 3), community radio corresponds, as all other forms of community media, to non-profit media that provide "community members with an opportunity to participate in the production process". For the International Association for Media and Communication Research, which supports a research group on Community Communication, this area includes media that originate from, circulate and resonate with the sphere of civil society.